Al-Jāḥiẓ (d. 255/869) on Ḥadīth Criticism - Sánchez, Ignacio (Journal of Abbasid Studies, 2015)
The notable and distinguished adīb and theologian of the third/ninth century, al-Jāḥiẓ, is usually not associated with the study of ḥadīth. On the contrary, he has frequently been considered a vitriolic critic of the experts on traditions and some of his works have even been interpreted as a demolition of the science of ḥadīth. However, a careful reading of his writings reveals a quite different picture. In this article, al-Jāḥiẓ’s treatises on the imamate — and especially the most extended one, the Kitāb al-ʿUthmāniyya — will be scrutinised and discussed in the light of the author’s acquaintance with the tradition of legal hermeneutics as described in al-Shāfiʿī’s Risāla.